Two new species and a new record of Gaeolaelaps Evans & Till (Acari: Laelapidae) from Altai Mountains, Russia - Joharchi, Omid; Döker, Ismail; Khaustov, Vladimir A. (Zootaxa, 2021)
This paper reports on three species of mites of the genus Gaeolaelaps from Altai Mountains, Russia. Gaeolaelaps altaiensis sp. nov., G. lenis Vatankhah & Nemati were collected from nests of Lasius sp. and Formica sp. (Hymenoptera: Formicidae), respectively, and G. euparadactylifer sp. nov. from moss on the shore of the Teletskoye Lake. The new species have the unusual character state of short peritremes, ending near the middle of coxae II. In G. euparadactylifer sp. nov., the pretarsal paradactyli on legs II–IV are strongly elongated, apically pointed and with their tips projecting well beyond the claws. Both new species are described based on morphological characters of the adults. In addition, the male of Gaeolaelaps lenis is described for the first time.